Practical Learning Innovation: Real Condition Video-Based Direct Instruction Model in Vocational Education - Warju Warju; Sudirman Rizki Ariyanto; Soeryanto Soeryanto; Rachmad Syarifudin Hidayatullah; Muhammad Nurtanto (Journal of Educational Science and Technology (EST), 2020)
This study aims to improve student learning outcomes through the implementation of direct learning models that are supported by learning videos. Class action research refers to Kemmis and McTaggart's designs, which are carried out over two cycles. The subjects of the study were students of class X LVE 7 at VHS Dharma Bahari Surabaya. Data were collected using test and observation instruments. Test and observation data were analyzed descriptively based on standardized study completeness criteria. The results of this study found that student learning outcomes consistently increased from the pre-test scores, the value of the first cycle, to the value of the second cycle. Based on the pre-test score data, it is known that there are 16 or 53% of 30 students who reach the complete category. Learning outcomes are then improved in the first cycle, where there are 19 or 63% who reach the complete category. Meanwhile, in cycle II there were 23 or 77% of students who reached the complete category. This increase occurred consistently so that it was concluded that the use of direct learning models supported by learning videos was very effective for the learning of class X LVE 7 students at VHS Dharma Bahari Surabaya.